Quantum speed limit in a qubit-spin-bath system. (10th November 2015) - Hou, Lu; Shao, Bin; Wei, Yong-Bo; Zou, Jian
Abstract: We investigate the behavior of quantum speed limit (QSL) time for a typical non-Markovian system, a central spin coupled to a spin star configuration. We connect the QSL time with an external control and show that the effectiveness of the external magnetic field, as well as the coupling strength, is related to the fundamental bounds that affect the maximum speed at which a quantum system can evolve in its state space. We also demonstrate that a spin bath with larger size may shorten the QSL time, while the upper state population plays an important role for the acceleration of quantum evolution in the memory surrounding.